2022
DOI: 10.1088/1361-6420/ac99fb
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary iterated Tikhonov regularization: convergence analysis via Hölder stability

Abstract: In this paper, we study the nonstationary iterated Tikhonov regularization method (NITRM) proposed by Jin et al. [19] to solve the inverse problems, where the inverse mapping fulfills a Holder stability estimate. The iterates of NITRM are defined through certain minimization problems in the settings of Banach spaces. In order to study the various important characteristics of the sought solution, we consider the non-smooth uniformly convex penalty terms in the minimization problems. In the case of noisy data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been highly focused on recently and some interesting results has been given, see [26,27,28] for example. Moreover, Mittal et al showed in [35] that the assumption 3 holds for many inverse problems.…”
Section: Convergence Ratementioning
confidence: 99%
“…It has been highly focused on recently and some interesting results has been given, see [26,27,28] for example. Moreover, Mittal et al showed in [35] that the assumption 3 holds for many inverse problems.…”
Section: Convergence Ratementioning
confidence: 99%